Using nanobiopsy of single brain tumour cells to investigate transcriptional reprogramming during standard treatment. (12th October 2019) - Elpidorou, Marilena; Actis, Paolo; Stead, Lucy
Abstract: Glioblastoma (GBM) is an incurable brain cancer because, despite aggressive standard treatment (consisting of surgery, radiation and Temozolomide chemotherapy), 100% of tumours recur. GBM tumours are characterised by significant intratumour heterogeneity, with genotypically or phenotypically distinct subpopulations of cells co-existing within each tumour. However, it is not yet known whether the inevitable recurrence of GBM is owing to Darwinian selection of inherently treatment resistant cells within the primary tumour, or the ability of cells to transcriptional reprogram and acquire treatment resistance properties. Knowing this is fundamental to developing more effective treatment for GBM: should we therapeutically target existing cells or their ability to reprogram? The only way to know this is to profile individual cells longitudinally, which has not been possible until now. Here we present a pioneering technology, known as nanobiopsy, which can longitudinally track the transcriptional profile of single GBM cells through standard treatment. The nanobiopsy allows injection or extraction of cytoplasmic material by electrowetting. We have proved that this technique is able to sample cytoplasmic fractions from cells without killing them, giving us the advantage to capture the transcriptional changes occurring through treatment using optimised scRNA sequencing protocols. We are applying this novel technology to help us identify treatment resistance modes and mechanisms to reveal novel targets for drug development.